Abstract 1122‐000222: Repeated Mechanical Thrombectomy for Recurrent Large Vessel Occlusion: A Meta‐Analysis of Individual Participant Data - Mohamed Elfil; Mohammad Aladawi; Mohamed Eldokmak; Ahmed Bayoumi; Eshak I Bahbah (Stroke: Vascular and Interventional Neurology, 2021)
Introduction: Mechanical thrombectomy (MT) has become the standard treatment of acute ischemic stroke (AIS) caused by large vessel occlusion (LVO), with different techniques used to achieve revascularization of the occluded vessel. However, early re‐occlusion of the target vessels could still take place in a considerable proportion of patients who already underwent MT for LVO. Therefore, we conducted this systematic review and individual participant data (IPD) meta‐analysis to provide more comprehensive evidence regarding the efficacy of repeat thrombectomy for recurrent LVO in early after successful first‐time MT. Methods: A computerized search on MEDLINE via PubMed, SCOPUS, Web of Science, EMBASE, and Cochrane library using the relevant keywords was performed. The retrieved references were screened, and the relevant data were extracted. STATA and SPSS were used to perform this IPD meta‐analysis. Results: Twenty studies were included, of which ten studies were observational studies (n = 21,251 patients) and 10 cases reports (n = 10 patients). Out of the included patients, 266 patients (62.78% females) were identified with recurrent LVO. The overall prevalence of recurrent LVO was 1.6%, 95% CI (1.0% to 2.8%), p<0.001. The mean age of the included patients was 65.67±16.23 years. Cardiac embolism was the most common cause of stroke in both times (52%). The median number of days between the first and second LVO was 15 days (IQR: 4–191). Regarding the National Institute of Health Stroke Scale (NIHSS), the first and second MT reduced it significantly (MD = ‐8.91, 95% CI: ‐10.02 to ‐7.82) and (MD = ‐5.97, 95% CI: ‐7.53 to ‐4.43), respectively, with a significant difference between both procedures (p = 0.001). The mean ASPECT after the first MT was 8.65±1.45, and after the second MT was 8.01±1.88. A significant weak correlation was observed between the ASPECT of first MT and NIHSS before it (r = ‐0.270, p = 0.001). Based on the thrombolysis in cerebral infarction (TICI) grading system, the first MT resulted in 57.3% complete perfusion, 42.1% partially filling, and 0.7% no/minimal filling, while the second MT resulted in 48% complete perfusion, 30% partially filling, and 6.67% no/minimal filling, with a significant difference between both MTs (p = 0.042). Regarding the modified Rankin scale (mRS) at 90 days after the first MT, “0” was the most frequent outcome (26.9%), followed by “2” (13.0%), “1” (12.4%), and “4” (7.3%). On the other hand, the 90‐day mRS after the second MT was categorized as the following: “6” in 13.5%, “3” in 13.5%, “2” in 11.9%, “1” in 11.9%, and “4” in 9.3%. Conclusions: In properly selected patients with recurrent LVO, repeated MT appears to be feasible and safe. A prior MT procedure should not discourage aggressive treatment as these patients may achieve similar rates of good clinical outcomes as those who undergo single MT.